Understanding of researcher behavior is required to improve data reliability. Issue 5 (31st January 2019) - Wass, Mark N; Ray, Larry; Michaelis, Martin
Abstract: Background: A lack of data reproducibility ("reproducibility crisis") has been extensively debated across many academic disciplines. Results: Although a reproducibility crisis is widely perceived, conclusive data on the scale of the problem and the underlying reasons are largely lacking. The debate is primarily focused on methodological issues. However, examples such as the use of misidentified cell lines illustrate that the availability of reliable methods does not guarantee good practice. Moreover, research is often characterized by a lack of established methods. Despite the crucial importance of researcher conduct, research and conclusive data on the determinants of researcher behavior are widely missing. Conclusion: Meta-research that establishes an understanding of the factors that determine researcher behavior is urgently needed. This knowledge can then be used to implement and iteratively improve measures that incentivize researchers to apply the highest standards, resulting in high-quality data.